Capped nonviral sequences at the 5' end of the mRNAs of Rice Hoja Blanca Virus RNA4 - Ramírez, B.C.; Garcin, D; Calvert, Lee A.; Kolakofsky, D; Haenni, AL (1995)
Subgenomic RNAs of both polarities corresponding to rice hoja blanca virus (RHBV) ambisense RNA4 were detected in RHBV-infected rice tissues. Total RNA extracted from RHBV-infected and noninfected rice tissues and RNA4 purified from RHBV ribonucleoprotein particles were used as templates for primer extension studies. The RNAs extracted from RHBV-infected tissues contain a population of RNA molecules with 10 to 17 nonviral nucleotides at their 5' end. The RNA-cDNA hybrids resulting from primer extension of such RNA molecules were specifically immunoselected with anti-cap antibodies, indicating that the subgenomic RNAs are capped and probably serve as mRNAs and that the additional nucleotides at their 5' end possibly derive from host mRNAs via a cap-snatching mechanism.